The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1063/1.1315329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyatomic ion structure on thin-film growth: Experiments and molecular dynamics simulations

Abstract: The experiments described here examine 25-100 eV CF 3 ϩ and C 3 F 5 ϩ ion modification of a polystyrene ͑PS͒ surface, as analyzed by x-ray photoelectron spectroscopy. The molecular dynamics computer simulations probe the structurally and chemically similar reactions of 20-100 eV CH 3 ϩ and C 3 H 5 ϩ with PS. CF 3 ϩ and C 3 F 5 ϩ each form a distribution of different fluorocarbon ͑FC͒ functional groups on PS in amounts dependent upon the incident ion energy, structure, and fluence. Both ions deposit mostly inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(118 citation statements)
references
References 84 publications
(128 reference statements)
7
111
0
Order By: Relevance
“…Moreover, ion beam experiments for CF x ϩ ions (x ϭ 1-3) have shown that both etching and deposition are sensitive to the F/C ratio as well as the incident ion energy [8,9,14]. Molecular dynamics simulations by Graves and coworkers have also focused on CF x ϩ (x ϭ 1-3) ion is also formed on the Si surface during the simulations, and net deposition results in the case of CF ϩ bombardment [16].…”
Section: Cf 2 Surface Interactions In C 3 F 8 and C 4 F 8 Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ion beam experiments for CF x ϩ ions (x ϭ 1-3) have shown that both etching and deposition are sensitive to the F/C ratio as well as the incident ion energy [8,9,14]. Molecular dynamics simulations by Graves and coworkers have also focused on CF x ϩ (x ϭ 1-3) ion is also formed on the Si surface during the simulations, and net deposition results in the case of CF ϩ bombardment [16].…”
Section: Cf 2 Surface Interactions In C 3 F 8 and C 4 F 8 Plasmasmentioning
confidence: 99%
“…Most recently, we have focused on C 3 F 8 and C 4 F 8 plasmas as these systems are finding increased use in the microelectronics industry because of their lower global warming potentials [48]. Many of the theoretical [15,16 ] and experimental [8,9, 49 ] studies of FCP's have shown that plasma ions have considerable influence over resulting film chemistries. Recently, we have shown that ions can also significantly influence molecule-surface interactions in these systems [39].…”
Section: Fluorocarbon Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore somewhat surprising that there is much that is not known about the chemistry by which treated surfaces are modified, largely because of the difficulties in monitoring the process experimentally. [1][2][3][4][5] Computational methods such as molecular dynamics (MD) simulations are therefore an important approach to the enhancement of our understanding of the chemical processes involved in plasma surface treatments, especially to determine the effect of major components of the complex plasma environment. 4,[6][7][8][9][10][11][12][13] Fluorocarbons are one of the most commonly used materials in plasma treatments of surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Computational methods such as molecular dynamics (MD) simulations are therefore an important approach to the enhancement of our understanding of the chemical processes involved in plasma surface treatments, especially to determine the effect of major components of the complex plasma environment. 4,[6][7][8][9][10][11][12][13] Fluorocarbons are one of the most commonly used materials in plasma treatments of surfaces. For instance, fluorocarbon plasma treatment has been used for reactive ion etching of silicon dioxide during the fabrication of semiconductor devices and for fluorination of polymer surfaces to produce films with high thermal and chemical resistance, high dielectric constants, and low friction coefficients.…”
Section: Introductionmentioning
confidence: 99%